2023
DOI: 10.1039/d2nr07019g
|View full text |Cite
|
Sign up to set email alerts
|

In situphosphoselenization induced heterointerface engineering endow NiSe2/Ni2P/FeSe2hollow nanocages with efficient water oxidation electrocatalysis performance

Abstract: Exploiting earth-abundant and highly effective electrocatalysts toward oxygen evolution reaction (OER) is critical for boosting water splitting efficiency. Herein, we proposed a novel one-step phosphoselenization strategy to fabricate a heterostructured...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Electrochemical water splitting represents a highly promising technological approach to the production of hydrogen for renewable energy conversion, encompassing the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). , In the actual electrocatalytic process, a larger voltage than the theoretical 1.23 V is required to overcome the energy barrier of the OER and HER . Although numerous scientists have worked to explore exceptional catalysts for boosting water electrolysis, more attention has been paid to improving the catalytic efficiency for merely one-half-reaction, which present several problems and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting represents a highly promising technological approach to the production of hydrogen for renewable energy conversion, encompassing the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). , In the actual electrocatalytic process, a larger voltage than the theoretical 1.23 V is required to overcome the energy barrier of the OER and HER . Although numerous scientists have worked to explore exceptional catalysts for boosting water electrolysis, more attention has been paid to improving the catalytic efficiency for merely one-half-reaction, which present several problems and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…7 Numerous studies have demonstrated that Ir-based and Ru-based catalysts are excellent OER catalysts and can effectively enhance the catalytic activity in the OER. 8 However, as noble metals, the scarcity and high price of Ir and Ru seriously restrict their widespread use. Hence, developing inexpensive, stable, and highly efficient catalysts for the OER is still extremely needed.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic activity of the catalyst is significantly correlated with its morphology. Metallene, a class of thin-layered two-dimensional (2D) materials with a thickness of several atomic layers, has garnered significant interest in electrocatalysis fields on account of its large-surface area and sufficient catalytic active sites. The synthesis of PdMo bimetallene with highly curved and ultrathin structures has been reported, which exhibited excellent ORR performance in alkaline electrolytes . In addition to morphology control, another approach to enhance catalytic activity is interface engineering by polymer functionalization. For example, Pt nanospines functionalized with polyallylamine (PAA) were synthesized, which effectively improved the ORR activity, selectivity, and durability because the loose PAA layer on the surface can effectively change the electronic structure of Pt atoms .…”
Section: Introductionmentioning
confidence: 99%